Green Hydrogen Production: Process Design and Capacity Expansion Integrating Economic and Operational Autonomy Objectives - Cárdenas, Andrés I.; Díaz-Alvarado, Felipe A.; Torres, Ana Ines (Industrial & engineering chemistry research, 2024)
Green hydrogen is an attractive energy vector due to its zero carbon emission in production and use, supporting many industries in their transition to cleaner operations. However, the production of green hydrogen has a fundamental challenge in resilience since it requires renewable energy (RE) systems that are subject to variability. This study develops an optimization-based decision-making framework for the design and capacity expansion of hydrogen production systems at a regional level. A novel resilience objective function that considers external RE-derived fluctuations as well as internal plant failures is proposed. An illustrative case study using data from five regions in Chile verifies that consideration of resiliency in the objective function results in a system that is able to overcome the variance without greatly increasing the equilibrium cost for hydrogen. These designs are based on dual-storage capacities with different expansion profiles.